Arterial and Venous 3D Fusion AV-3D-DSA: A Novel Approach to Cerebrovascular Neuroimaging - Raz, E.; Shapiro, M.; Mir, O.; Nossek, E.; Nelson, P.K. (American Journal of Neuroradiology, 2021)
SUMMARY: DSA is the standard imaging technique for evaluation of cerebrovascular conditions. However, One drawback is its limitation in depicting a single angiographic phase at a time. We describe a new 3D-DSA algorithm, which we call arterial and venous-3D-DSA, which allows the concurrent yet distinct display of the arterial and venous structures, which may be useful for different clinical and educational purposes.AV-3D-DSAarterial and venous 3D-DSA